Categorically Jewish, distinctly Polish : Polish Jewish history reflected and refracted - Rosman, Moshe (Liverpool : Liverpool University Press, 2022)
Moshe Rosman's revolutionary approach has become a cornerstone of Polish Jewish historiography. Challenging conventions, he asserts that the 'marriage of convenience' between the Jews and the Polish--Lithuanian Commonwealth was a dynamic relationship that, though punctuated by crisis and persecution, developed into a saga of overall achievement and stability. With that fundamental message this book forges a thematic survey of Jewish history in early modern Poland. These essays, written by Rosman over the course of a distinguished career, have all been updated and enhanced with new detail and nuanced arguments, taking account not only of new archival material and research but also of the ongoing evolution of the author's own knowledge and perspectives. Some appear here in English for the first time. The volume's structure highlights key topics for understanding the Polish Jewish past: relations between Jews and other Poles; Jewish communal life; Polish Jewish women; and hasidism. O ...
Cover -- Contents -- List of Abbreviations -- Note on Transliteration -- Note on Place Names -- Maps -- Introduction -- Part 1: Historiography -- Introduction -- 1. A New Scholarly Foundation: The Historiography of Polish Jewry since 1945 -- 2. The Verdict of Israeli Historiography on Hasidism -- 3. POLIN: The Museum of the History of Polish Jews and the New Polish Jewish Metahistory -- Part 2: Jews and other Poles -- Introduction -- 4. Jewish Perceptions of Persecution and Powerlessness in the Commonwealth -- 5. A Minority Views the Majority Jewish Attitudes towards the Commonwealth and Interaction with Poles -- 6. Dubno in the Wake of Khmelnytsky -- 7. The Question of the Jews in the Constitution of the Third of May -- Part 3: The Jewish Community -- Introduction -- 8. Jewish Autonomy in Poland and the Polish Regime -- 9. The Authority of the Council of Four Lands Outside Poland-Lithuania -- 10. The Indebtedness of the Lublin Kahal in the Eighteenth Century -- 11. Everyday Violence in Jewish Communities of the Commonwealth -- 12. The Image of Poland as a Torah Centre after 1648 -- Part 4: Women -- Introduction -- 13. History of Jewish Women in the Commonwealth I: An Assessment -- 14. History of Jewish Women in the Commonwealth II: From Facilitation to Participation -- 15. Leah Horowitz's Tkhine imohos: A Proto-Feminist Demand to Increase Jewish Women's Religious Capital -- Part 5: Hasidism -- Introduction -- 16. The Rise of Hasidism -- 17. Miedzyboz and Rabbi Israel Ba'al Shem Tov -- 18. Stories that Changed History: The Unique Career of Shivhei habesht -- 19. Hasidism as a Modern Phenomenon -- Conclusion: Theme Decoding -- Bibliography -- Index.
"Littman Library of Jewish Civilization"
eBooks on EBSCOhost
Keywords: Jews -- Poland -- History; Juifs -- Pologne -- Histoire; Jews; Poland; European history; History; History